Concentration and temperature induced dual-responsive wormlike micelle to hydrogel transition in ionic liquid-type surfactant [C16imC9]Br aqueous solution without additives1. Issue 28 (28th July 2015) - Hu, Yimin; Ge, Lingling; Han, Jie; Guo, Rong
<x xml:space="preserve">Abstract</x> A viscoelastic fluid formed by [C16imC9]Br and water without any additive is studied, which shows rheological behavior as a function of both concentration and temperature that invokes a transition between wormlike micelles and hydrogels.